2002
DOI: 10.1073/pnas.112202799
|View full text |Cite
|
Sign up to set email alerts
|

Protein–protein interactions among C-4 demethylation enzymes involved in yeast sterol biosynthesis

Abstract: A Saccharomyces cerevisae microarray expression study indicated that an ORF, YER044C, now designated ERG28, was strongly coregulated with ergosterol biosynthesis. Disruption of the ERG28 gene results in slow growth and accumulation of sterol intermediates similar to those observed in erg26 and erg27 null strains, suggesting that the Erg28p may interact with Erg26p and/or Erg27p. In this study, a peptide from human hemagglutinin protein (HA) epitope tag was added to ERG26 and ERG27 genes, and a Myc tag was adde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
63
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 19 publications
1
63
0
Order By: Relevance
“…During the course of our studies, Marijanovic et al (33) demonstrated that the protein encoded by the human HSD17B7 locus functions as a cholesterol biosynthetic 3-ketosterol reductase. In Saccharomyces cerevisiae, the ERG28 gene encodes a regulatory protein for the complex that may act as a scaffold and anchor the C-4 demethylase enzymes to the ER membrane (34,35). Consistent with this model, our results showed upregulation of Sc4mol, Hsd17b7, and Orf11, the murine ortholog of ERG28 (34), in Bpa 1H cells grown in LDS.…”
Section: Discussionsupporting
confidence: 76%
“…During the course of our studies, Marijanovic et al (33) demonstrated that the protein encoded by the human HSD17B7 locus functions as a cholesterol biosynthetic 3-ketosterol reductase. In Saccharomyces cerevisiae, the ERG28 gene encodes a regulatory protein for the complex that may act as a scaffold and anchor the C-4 demethylase enzymes to the ER membrane (34,35). Consistent with this model, our results showed upregulation of Sc4mol, Hsd17b7, and Orf11, the murine ortholog of ERG28 (34), in Bpa 1H cells grown in LDS.…”
Section: Discussionsupporting
confidence: 76%
“…At3␤HSD/D1 and ⌬-At3␤HSD/D2 restored growth, high levels of ergosterol biosynthesis, and in vitro high catalytically competent 3␤HSD/Ds localized exclusively in the corresponding microsomal extracts. In contrast to most SDR proteins, including HSDs, biochemical studies performed in animals (39), yeast (40), and plants (5) have shown that native 3␤HSD/D is membrane-bound. Although a single hydrophobic portion was found in the Arabidopsis 3␤HSD/D1 and ⌬-At3␤HSD/D2 proteins, the activities of both recombinant At3␤HSD/Ds containing an ER retrieval signal were found in the corresponding microsomal extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies performed in yeast have elucidated the protein-protein interactions with regard to sterol biosynthesis and particularly the C-4 demethylation complex (40,41). Functional association of At3␤HSD/Ds with the C-4 demethylation complex could involve a limited number of amino acid interactions, including charged pairing between the partners as shown in a number of membrane-bound electron transfer complexes such as the cytochrome b 5 -cytochrome b 5 reductase (42,43) or the cytochrome P450-cytochrome P450 reductase (44) complexes.…”
Section: Discussionmentioning
confidence: 99%
“…We subsequently demonstrated that Erg28p is an endoplasmic reticulum (ER) transmembrane protein, working as a transmembrane scaffold to tether Erg27p and possibly other C-4 demethylation proteins (Erg25p, Erg26p) to form a demethylation complex in the ER (12). More recent studies also indicated that Erg28p not only anchors the C-4 demethylation enzyme complex to the ER but also acts as a tether to Erg6p, a side chain transmethylation enzyme required for a downstream reaction in sterol biosynthesis (13) (Fig.…”
mentioning
confidence: 99%